Kemampuan Pemahaman Matematis Siswa Melalui Model Pembelajaran Auditory Intellectualy Repetition dan Problem Based Learning - Alan, Usman Fauzan; Afriansyah, Ekasatya Aldila (Mathematics Education Journal, 2017)
The purpose of this study are: (1) To determine the ability of understanding mathematical difference between students who had Auditory Intellectual Repetition learning model and Problem Based Learning model. This research is a quasi-experimental research, pretest-posttest Control Design. The population in this study were all students of VII class SMP Negeri 1 Cisurupan by taking a sample of two classes of VII-A class as an experimental 1st class and VII-B class as the experimental 2nd class. The research instrument used is to test the ability of mathematical understanding. Based on the research, we found that: There were differences in the ability of mathematical understanding among students who earn AIR learning model and PBL model.